PENGARUH PENGOLAHAN DAN PENYIMPANAN TERHADAP PENERIMAAN SENSORI DAN AKTIVITAS ANTIOKSIDAN MINUMAN HERBAL BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) - Vina Lustiana; Alia Rahmi; Agung Nugroho; Anhar Firdaus (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
Bawang Dayak (Eleutherine palmifolia (L.) Merr.) is a plant that is often utilized by the community as a traditional medicine because it contains active compounds that have antioxidant activity. People usually prepare them by boiling. In this study, bawang dayak are processed to herbal drinks to determine the antioxidant activity during storage. The study aims of this research is to determine the best bawang dayak herbal drink based on antioxidant activity and sensory attributes by studying the effect of the processing (raw material and sweetener composition) and storage. This research uses factorial design method with randomized block design with grouping in storage time of day 0 and day 7. Factor I consists of 2 levels: fresh bawang dayak and dried bawang dayak, while factor II is unsweetened and sweetened (sucrose). The analysis were the presence of phytochemical compounds, acidity (pH), antioxidant activity (DPPH method), and sensory analysis (hedonic 1-5). The results showed that bawang dayak herbal drink made from dried herbs (40 g in 1 L water) processed by boiling for 10 minutes, and stored for 7 days showed the best antioxidant activity with the value of % inhibition of 71.49%, and IC50 of 6.15 mg/ml, sensory attributes of hedonic scale of 2.9 for color (like slightly), 2.5 for aroma (like slightly) and 2.6 for taste (like slightly).